Arrested development and increased incidence of sandprawn embryonic aberrations along an intertidal human recreation gradient - K. A. Madell; U. M. Scharler; C. Savage; A. M. L. Karlson; D. Pillay (Scientific Reports)
Abstract Anthropogenic pressures are increasing in coastal ecosystems globally, yet identifying robust indicators of change and managing coastal resources can be complicated by phenotypic plasticity and differential life-history responses of key organisms. We illustrate this using biogeochemical and sandprawn (Kraussillichirus kraussi) response metrics along a human recreation gradient (trampling, sandprawn harvesting) in a South African lagoonal ecosystem. Benthic compaction, oxygen depletion and high porewater ammonia concentrations were associated with greatest recreation intensity. Sandprawn abundance was similar across the recreation gradient and body condition was counter-intuitively greater in areas with maximum recreation, but with higher frequencies of embryonic aberrations and arrested development. These findings suggest different vulnerabilities of life-history stages of sandprawns to recreation, with embryonic stages being highly susceptible. We suggest that embryonic aberrations and developmental changes in endobenthic crustaceans may be sensitive bioindicators of recreation-induced changes in sedimentary systems.